2020
DOI: 10.1200/jco.2020.38.4_suppl.132
|View full text |Cite
|
Sign up to set email alerts
|

Pertuzumab plus trastuzumab (P+T) in patients (Pts) with colorectal cancer (CRC) with ERBB2 amplification or overexpression: Results from the TAPUR Study.

Abstract: 132 Background: TAPUR is a phase II basket trial evaluating anti-tumor activity of commercially available targeted agents in pts with advanced cancers with genomic alterations. Results in a cohort of CRC pts with ERBB2 overexpression or amplification treated with P+T are reported. Methods: Eligible pts had advanced CRC, no standard treatment (tx) options, measurable disease, ECOG PS 0-2, and adequate organ function. Genomic testing was performed in CLIA-certified, CAP-accredited site selected labs. Pts had ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…Another phase II basket study, TAPUR, also investigated the combination of trastuzumab and pertuzumab in HER2-amplified mCRC. 302 In this study, 28 patients with heavily pretreated, HER2-amplified advanced CRC were treated with the combination. Four partial responses and 10 cases of stable disease for at least 16 weeks were reported, leading to a disease control rate of 50% and an ORR of 14%.…”
Section: Trastuzumab Plus Pertuzumabmentioning
confidence: 99%
“…Another phase II basket study, TAPUR, also investigated the combination of trastuzumab and pertuzumab in HER2-amplified mCRC. 302 In this study, 28 patients with heavily pretreated, HER2-amplified advanced CRC were treated with the combination. Four partial responses and 10 cases of stable disease for at least 16 weeks were reported, leading to a disease control rate of 50% and an ORR of 14%.…”
Section: Trastuzumab Plus Pertuzumabmentioning
confidence: 99%
“…For example, the Molecular Screening for Cancer Treatment Optimization (MOSCATO 01) study demonstrated that targeted therapy, which was matched to a genomic alteration, improved the survival of 33% (63/193) of the study participants [ 4 ]. In addition, in the Targeted Agent and Profiling Utilization Registry (TAPUR) study, genomically matched treatment showed good clinical efficacy in the following five cohorts: pertuzumab and trastuzumab in ERBB2 -amplified or overexpressed colorectal cancer [ 6 ], emurafenib and cobimetinib in BRAF V600E/D/K/-mutated colorectal cancer [ 7 ], pembrolizumab in metastatic breast cancer with a high mutational burden [ 8 ], pembrolizumab in metastatic colorectal cancer with a high mutational burden, and palbociclib in non-small cell lung cancer with CDKN2A alteration [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 9.7% ORR achieved by HERACLES-B regimen, lower than the 30% in HERACLES-A, should not dampen the interest for target-treating HER2+ mCRC; on the contrary, it underlines that several effective therapeutic options are at hand, including trastuzumab-based combinations with either small molecules tyrosine kinase inhibitors 7 or monoclonal antibody, such as pertuzumab aimed, at different epitopes. 17 24 Interestingly, recent data of the HER2+ mCRC arm of the Targeted Agent and Profiling Utilisation Registry study showed despite a higher ORR (25%) with the combination of trastuzumab and pertuzumab, 25 as data of the KRAS wild-type cohort of the MyPathway trial, a similar PFS of 4.3 months, once again indicating that a maintained disease control may be indicative of the antitumour potential of a HER2 therapeutic blockade. Other emerging therapeutic strategies include the development of more potent anti-HER2 agents, 26 such as bispecific antibodies which can bind two non-overlapping epitopes on HER2 or engage immune mediators together with HER2 binding, and novel antibody-drug conjugates such as trastuzumab deruxtecan.…”
Section: Discussionmentioning
confidence: 99%